REAKTIFITAS BERBAGAI JENIS PELARUT DARI RESIDU KILANG MINYAK PLAJU PADA PENCAIRAN BATUBARA BANKO TENGAH - Hartiniati Hartiniati (Badan Pengkajian dan Penerapan Teknologi, 2009)
An effect of two different residue for liquefaction of Central Banko coal isdisccused. The residue was obtained from side-stream of refinery plant, whichso-called long residue and short residue solvents. The liquefaction test wascarried out under the reference conditions that have been developed in BPPTcoal liquefaction laboratory, at temperature of 450oC and initial H2 pressure of12MPa for 1 hour. The result shows that the distillate yield, Bottom (BTM) yield,and hydrogen consumption were dependent on the nature of solvent. Shortresidue solvent shown higher reactivity than the long residue. Reaction betweenCentral Banko and Short Residue gave distillate yield higher than the longresidue. Moreover, its BTM yield was also lower than that of long residue solvent.This result confirmed the lower hydrogen consumption for reaction short residueand Central Banko coal compared to that for reaction long residue and CentralBanko. In this study, it also confirmed that the yield of H2O and CO+CO2 weredependent on the material input condition. However, the yield of hydrocarbongases (C1 C4) was mainly affected by de-alkylation in the solvent and coal duringthe reactionKata kunci: residu minyak bumi, proses pencairan batubara, central Banko